Translating the biology of aging into novel therapeutics for Alzheimer disease. (8th January 2019) - Hara, Yuko; McKeehan, Nicholas; Fillit, Howard M.
Abstract : Aging is the leading risk factor for most chronic illnesses of old age, including Alzheimer disease (AD), a progressive neurodegenerative disease with currently no therapies that prevent, slow, or halt disease progression. Like other chronic diseases of old age, the progressive pathology of AD begins decades before the onset of symptoms. Many decades of research in biological gerontology have revealed common processes that are relevant to understanding why the aging brain is vulnerable to AD. In this review, we frame the development of novel therapeutics for AD in the context of biological gerontology. The many therapies currently in development based on biological gerontology principles provide promise for the development of a new generation of therapeutics to prevent and treat AD.